HUBUNGAN ANTARA SELF CONTROL DENGAN INTERNET ADDICTION PADA REMAJA - Endah Sulistio N; Dewi Puspo R; Dina Dwi I; Husni Anggoro; Muhammad Ervin S; Starry Kireida K (Fakultas Psikologi Universitas Wijaya Putra, 2020)
The purpose of this study was to see how the relationship between self control and internetaddiction in adolescents. The lower the self control, the internet addiction will increase.Self control is the ability to control yourself, internet internet users who have high selfcontrol are able to regulate the use of the internet so that it does not sink into the internet,able to use the internet as needed, able to integrate online activities with other activities inhis life. Teenagers who cannot control themselves in using the internet will depend on theinternet which is commonly called internet addiction. Internet addiction can be interpretedas a syndrome characterized by individuals spending a very large amount of time using theinternet and cannot control their use while online. This study uses a quantitativecorrelational design method. The scale used is the self control scale and the internetaddiction scale that has been adapted. The results showed that there was a significantrelationship between Sig. (2-tailed) between self control and internet addiction is 0,000<0.05. Furthermore, the relationship between self control and internet addiction is 0,000<0.05. While the calculated value of r for the relationship of self control and internetaddiction is equal to - 0.770 <r table 0.279, it is concluded that there is a relationshipbetween variables. Because r count or Pearson Corellations is negative, which means thehigher the self control, the lower the internet addiction, and vice versa the lower the selfcontrol, the higher the internet addiction.